When "Blended" Becomes "Online". (4th January 2022) - Foung, Dennis; Chen, Julia; Lin, Linda
Abstract : With the outbreak of COVID-19 in 2020, many universities shifted to online teaching. However, some online instruction had already been implemented well before the pandemic. This study investigates (1) how engagement in blended CALL activities differed during the pandemic, and (2) in what ways the assessment outcomes were associated with student engagement during the pandemic. The study was conducted in an English for academic purposes (EAP) course at a Hong Kong university that had already implemented blended learning for several years. Adopting an analytics-based approach, 469, 286 data logs in a learning management system were analyzed to measure students' engagement and their respective self-directed behavior. The retrieved student data covered the time both before and during the pandemic. Our findings reveal that students were primarily engaged for assessment purposes; however, those in the pandemic cohort demonstrated better self-directed behavior, such as early and regular engagement. Although the results indicated a relatively strong association between student engagement and course outcomes, the students during the pandemic seem to have managed their learning more effectively.